Commonly missed nursing cares in the obstetrics and gynecologic wards of Tigray general hospitals; Northern Ethiopia. - Mebrahtom Haftu; Alem Girmay; Martha Gebremeskel; Gebrekiros Aregawi; Dawit Gebregziabher; Carmen Robles (PLoS ONE)
Background Missed nursing care is considered an error of omission and is defined as any aspect of required patient care that is omitted (either in part or whole) or significantly delayed. Nursing care missed in the perinatal setting can cause negative outcomes and repercussions for the quality and safety of care. This has been reported in multiple settings and countries and is tied to negative maternal outcomes. Preventing missed nursing care requires in-depth research considering the clinical setting. Objective The main aim of the study was to assess commonly missed nursing care elements, reasons, and factors for the omission in the obstetric and gynecologic units of general hospitals in Tigray 2017/18. Methods and materials A cross-sectional study was conducted in eight randomly selected general hospitals in Tigray, Ethiopia. A total of 422 nurses and midwives were selected through simple random sampling using the staff list as a sampling frame. To identify the commonly missed nursing care and related factors, the MISSCARE survey tool was used. Descriptive, bivariate, and multivariate logistic regression analysis was performed to assess potential risk factors of nursing cares omission. Result The study results showed that 299 (74.6%) participants commonly missed at least one nursing care in the perinatal setting. Labor resources 386(96.3%), teamwork 365(91%), material resources 361 (90%) and communication 342 (85.3%) were the reasons identified for commonly missing care. In the multivariate analyses, sex (p-value <0.001), educational level (p-value 0.034), working shift (p-value <0.001) and having an intention to leave the institution (p-value <0.001) showed a significant association with commonly missing care. Conclusion The proportion of commonly missed nursing care was high. After adjusting for demographic variables, labor resources, material resources, and communication were reasons for commonly missed nursing care. Increasing male professional proportion, investing in nurses/midwives training, and harmonizing nursing service administration through appropriate working shift arrangement and timely assessment of professionals' stability and satisfaction could minimize frequent omission of nursing care.